Drug administration errors in paediatric wards: a direct observation approach - Chua, S.S.; Chua, H.M.; Omar, A. (2010)
Paediatric patients are more vulnerable to drug administration errors due to a lack of appropriate drug dosages and strengths for use in this group of patients. Therefore, the aim of the present study was to determine the extent and types of drug administration errors in two paediatric wards and to identify measures to reduce such errors. A researcher was stationed in two paediatric wards of a teaching hospital to observe all drugs administered to paediatric inpatients in each of the ward, for 1 day in a week over ten consecutive weeks. All data were recorded in a data collection form and then compared with the actual drugs and dosages prescribed for the patients. Of the 857 drug administrations observed, 100 doses had errors, and this gave an error rate of 11.7 95% confidence interval (CI) 9.5-13.9%. If wrong time administration errors were excluded, the error rate reduced to 7.8% (95% CI 6.0-9.6%). The most common types of drug administration errors were incorrect time of administration (28.8%), followed by incorrect drug preparation (26%), omission errors (16.3%) and incorrect dose (11.5%). None of the errors observed were considered as potentially life threatening, although 40.4% could possibly cause patient harm. Drug administration errors are as common in paediatric wards in Malaysia as in other countries. Double-checking should be conducted, as this could reduce drug administration errors by about 20%, but collaborative efforts between all healthcare professionals are essential.